Innovation in Making of Tongseng Using Dragon Fruit Skin Raw Materials - Dewangga, Ferdian Bagus; Larasati, Sri (Gastronary, 2023)
T The research with the title "Innovation in Making Tongseng With Dragon Fruit Skin Raw Materials" the researchers conducted this experiment to determine how respondents responded to tongseng innovation products made from dragon fruit skin from indicators of taste, texture, scent, colour and appearance, as well as utilizing red dragon fruit skin waste that should be appropriately processed. This type of research is a quantitative study, where the respondents in this study are residents of Perum Puri Sendangtirto Gandu village, STP AMPTA students, employees of R&B Grill Real Steak Yogyakarta, and experts who have taken from STP AMPTA lecturers with a total of 30 people. The data analysis method to test the hypothesis uses friedman test analysis and hedonic test, Based on the Hedoni Test table, it can be concluded that the acquisition of hedonic tests carried out during the questionnaire process from all five aspects (taste, texture, aroma, warm and appearance) HO1 was rejected because of the 3 indicators (taste, aroma, appearance) dominant said Very Like and Like so that it can be interpreted that the processed Dragon Fruit Tongseng and can be used as an innovative product. While the study used the Friedman test with statistical test results, it was known that the value of Asymp.  Sig.  of 0.000 or (<0.05). So using the method of soaking whiting water deserves to be an innovative product of processed tongseng. Based on the Test Static output table, it is also known that the Chi-Square Count value is 64,799, while the Chi-Square Table value is for df; 5% ( 4;0.05) is 9.488. The value of the Chi-Square Count of 64,799 is greater than the Chi-Square Table of 9,488, so it can be concluded that Ho2 is rejected, which means "processed dragon fruit skin tongseng can be used as an innovative product".